High anti-corrosion barrier of poly (methyl methacrylate)-silica coatings explained: A thousand-days study - Uvida, Mayara Carla [UNESP]; Trentin, Andressa [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Hammer, Peter [UNESP] (Elsevier, 2024)
Poly (methyl methacrylate) (PMMA)-silica coatings form a few micrometers thick anti-corrosive barrier that blocks corrosive species when exposed to harsh environments. Their excellent anti-corrosive performance stands out for protecting metal alloys immersed in seawater for long periods (>2 years), making them compliant for applications in the marine, aeronautical, and automotive industries. A key approach to understanding the degradation of high-performance coatings over time consists of analyzing their water uptake-induced structural changes. This work examines in detail the uptake and structural modification of PMMA-silica coatings on Al alloys immersed for more than 1000 days in 3.5 wt% NaCl solution. Gravimetry, thermal analysis, infrared spectroscopy and electrochemical impedance spectroscopy (EIS) were employed to monitor the evolution of coated samples. Nuclear magnetic resonance, X-ray photoelectron spectroscopy, electron and atomic force microscopies before and after immersion indicate a slight leaching-induced surface roughening due to silica hydrolysis. These findings comply with the low uptake values (∼0.6 vol%) and a less-Fickian diffusion coefficient obtained from modelling of the EIS data. The high impedance modulus (>GΩ) is related to the highly cross-linked structure, resulting in a very low permeation rate of the electrolyte. The applied methodology is of crucial importance for establishing a standardized analysis for high-performance protective coatings.
Keywords: Aluminum alloy; EIS; High-performance coatings; PMMA-silica; Water uptake